Optical detection of ballistic electrons injected by a scanning-tunneling microscope - Kemerink, Martijn; Sauthoff, Katharina; Koenraad, Paulus M.; Gerritsen, J. W.; van Kempen, H.; Wolter, Joachim H. (Physical review letters, 2001)
We demonstrate a spectroscopic technique which is based on ballistic injection of minority carriers from the tip of a scanning-tunneling microscope into a semiconductor heterostructure. By analyzing the resulting electroluminescence spectrum as a function of tip-sample bias, both the injection barrier height and the carrier scattering rate in the semiconductor can be determined. This technique is complementary to ballistic electron emission spectroscopy since minority instead of majority carriers are injected, which give the opportunity to study the carrier trajectory after injection.